A Qualitative Comparison of ANSYS and OpenFOAM results for Carbon dioxide Plume Transport - S Madsen; Z Andleeb; H Khawaja; G Boiger; M Moatamedi (International Journal of Multiphysics, 2023)
This research presents Computational Fluid Dynamics (CFD) simulations in ANSYS® illustrating emissions of to the air. The CFD simulations is employed to study plume transport in urban environment, i.e., Breivika port in the city of Tromsø. The case study presents a two-phase model considering specific wind strength and direction in the city of Tromsø. Geographical coordinates, temperature, and wind data were obtained from the open sources, such as Google Maps, and Norwegian Meteorological Institute. The results from the simulations indicates a potential outcome with respect to various weather conditions. It was revealed for vessels less than 30 meter chimney height, the higher the wind strength, the lower the plume dispersion, causing the plume to stay closer to the terrain. This brings in a concentrated amount of pollutants closer to the public areas. The terrain in the model is recognizable for the Tromsø port’s location. From the CFD results, it is illustrated that onshore wind with high wind strength could affect the environment. The results simulated in OpenFOAM are qualitatively showing the same as visible in ANSYS®.